2013
DOI: 10.1016/j.juro.2012.11.121
|View full text |Cite
|
Sign up to set email alerts
|

Surgically Induced Chronic Kidney Disease May be Associated with a Lower Risk of Progression and Mortality than Medical Chronic Kidney Disease

Abstract: Surgically induced chronic kidney disease is associated with a relatively low risk of progressive renal functional decline and impact on survival does not appear to be substantial during intermediate term followup. In contrast, preoperative chronic kidney disease due to medical causes places patients at increased risk, indicating nephron sparing surgery for such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
194
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(207 citation statements)
references
References 24 publications
10
194
0
3
Order By: Relevance
“…These findings bolster other recent reports, which suggest that surgically induced CKD may not be associated with the same degree of renal functional decline as CKD that may be caused by medical factors [2,3]. While the incidence of de novo stage III CKD (36.1%) and delta estimated GFR between preoperative and postoperative values are lower than reported by most other groups, which may be attributable to national and demographic trends that are different from North American and European trends [2][3][4], the findings are nonetheless important and show that in the short-to-intermediate term (median follow up of 33 months) continued renal functional stabilisation and recovery occurs after RN. Also, performing a RN in a patient does not sentence him or her to invariable or inevitable renal functional decline in the short-to-intermediate term.…”
Section: Renal Functional Recovery After Radical Nephrectomysupporting
confidence: 87%
See 1 more Smart Citation
“…These findings bolster other recent reports, which suggest that surgically induced CKD may not be associated with the same degree of renal functional decline as CKD that may be caused by medical factors [2,3]. While the incidence of de novo stage III CKD (36.1%) and delta estimated GFR between preoperative and postoperative values are lower than reported by most other groups, which may be attributable to national and demographic trends that are different from North American and European trends [2][3][4], the findings are nonetheless important and show that in the short-to-intermediate term (median follow up of 33 months) continued renal functional stabilisation and recovery occurs after RN. Also, performing a RN in a patient does not sentence him or her to invariable or inevitable renal functional decline in the short-to-intermediate term.…”
Section: Renal Functional Recovery After Radical Nephrectomysupporting
confidence: 87%
“…Notwithstanding the limitations of this retrospective, non-comparative, single-centre study, it is clear that the perioperative, oncological and short-term functional outcomes reported at this medium-volume centre are by and large similar to those from other high-volume RP centres [2,3]. Overall morbidity is low, and the length of stay is relatively short (i.e.…”
Section: Mid-term Uk Outcomes Data After Extraperitoneal Laparoscopicmentioning
confidence: 64%
“…The importance of preoperative eGFR on predicting surgical outcomes, such as postoperative renal function and even all-cause mortality rates, has been verified by other studies. 6 However, it is increasingly known that using equations to estimate GFR based on serum creatinine alone may be suboptimal to predict or evaluate postsurgery kidney function in patients with kidney cancer, 12 primarily because the characteristics of the population used for the development of various equations such as MDRD differ from that of the kidney cancer population.…”
Section: Discussionmentioning
confidence: 99%
“…CKD-M is caused by medical renal diseases and places patients at a higher risk of progressive renal decline compared with CKD-S, which is caused by an acute insult such as surgical removal of functioning nephrons (nephrectomy or partial nephrectomy). 6 CKD-S has been proposed to be a separate entity that impacts less on survival and long-term function in patients without CKD-M, 6 but compounds the impact in patients with CKD-M already (CKD-M/S). 7 These findings suggest that the definition and classification of CKD based solely on GFR may not accurately reflect the extent of kidney disease in patients developing CKD-S. As CKD-S results in reduced complement of nephrons, kidney volume would theoretically be an ideal anatomical representation of kidney reserve.…”
Section: Introductionmentioning
confidence: 99%
“…Is it possible to improve patient's prognosis? Lane et al [12] examined the association between postoperative GFR and overall survival in cohort of 4180 patients who are undergone radical or partial nephrectomy. In their study, they confirmed, although GFR did not predict survival in patients with normal pre-operative renal function, in those who with pre-existing chronic kidney disease (GFR <60 mL/min per 1.73 m 2 ) from medical causes, lower post-operative GFR is associated with increased mortality independent of age and comorbidities.…”
Section: Discussionmentioning
confidence: 99%